Cross-cultural psychology : research and applications. - Berry, John Widdup, 1939-; Breugelmans, Seger M., ....-; Poortinga, Ype Hendrikus, 1939- (Cambridge : Cambridge University, 2012)
Cross-Cultural Psychology is a leading textbook offering senior undergraduate and graduate students a thorough and balanced overview of the whole field of cross-cultural psychology. The team of internationally acclaimed authors present the latest empirical research, theory, methodology and applications from around the world. They discuss all domains of behavior (including development, social behavior, personality, cognition, psycholinguistics, emotion and perception), and present the three main approaches in cross-cultural psychology (cultural, culture-comparative, and indigenous traditions) as well as applications to a number of domains (including acculturation, intercultural relations and communication, work and health). With new additions to the writing team, the third edition benefits from an even broader range of cross-cultural perspectives. Now in 2-colour, the format is even more reader-friendly and the features include chapter outlines, chapter summaries, further reading and an updated glossary of key terms. This edition also offers an accompanying website containing additional material and weblinks. Contents 1. Introduction; Part I. Similarities and Differences in Behavior Across Cultures: 2. Individual development: infancy and early childhood; 3. Individual development: childhood, adolescence and adulthood; 4. Social behavior; 5. Personality; 6. Cognition; 7. Emotion; 8. Language; 9. Perception; Part II. Relationships Between Behavior, Culture and Biology: 10. Contributions of cultural anthropology; 11. Contributions of evolutionary biology; 12. Methodology and theory; Part III. Applying Research Findings Across Cultures: 13. Acculturation; 14. Intercultural relations; 15. Intercultural communication and training; 16. Work and organizations; 17. Health; 18. Culturally informed and appropriate psychology; Epilogue; Glossary of key terms.
Keywords: Cross-culturele psychologie